Susceptibility-Guided Therapy vs. Bismuth-Containing Quadruple Therapy as the First-Line Treatment for Helicobacter pylori Infection: A Systematic Review and Meta-Analysis - Ouyang, Yaobin; Zhang, Wenjing; He, Chen; Zhu, Yin; Lu, Nonghua; Hu, Yi (Frontiers in Medicine, 2022)
Background: The increased antibiotics resistance of Helicobacter pylori (H. pylori) lead to the decreased efficacy of H. pylori regimens. Aim: To evaluate the efficacy, safety and compliance of susceptibility-guided therapy (SGT) versus bismuth containing quadruple therapy (BQT) as the first-line treatment for H. pylori infection. Materials and Methods: This meta-analysis was performed in accordance with the PRISMA 2009 guidelines. A systematic search of the Pubmed, Embase, and Cochrane database was conducted using the combination of “Helicobacter pylori or H. pylori or Hp”, “bismuth quadruple” and “tailored eradication OR tailored therapy OR susceptibility-guided therapy OR personalized therapy OR antibiotic susceptibility testing”. Results: 8 studies with 2893 H. pylori-infected patients were enrolled. The pooled eradication rate of SGT and BQT were 85.1% versus 81.8% (P>0.05) and 91.2% versus 89.4% (P>0.05) by ITT and PP analysis, respectively. SGT has a significant superior efficacy than BQT (pooled RR = 1.14, 95% CI, 1.08-1.20, P < 0.05) in the subgroup of culture with susceptibility test. Similar efficacy of SGT and BQT was observed in the subgroup analysis of Dual-priming oligonucleotide-based multiplex polymerase chain reaction test (pooled RR = 0.95, 95% CI, 0.88-1.02, P = 0.147). The pooled side effects rate was 21.7% in SGT and 24.6% in BQT, which showed no significant difference (P>0.05). The compliances of SGT and BQT were 97.0% and 96.0%, respectively. Conclusion: SGT and BQT shows similarly high efficacy, safety and good compliance in the first-line treatment for H. pylori infection in areas with high antibiotics resistance. The decision-making of first-line regimens for H. pylori infection should depend on the availability, cost-effectiveness of susceptibility test and bismuth in local areas.